Cultivo de macroalgas e desenvolvimento de extratos brutos visando produção de insumos para indústria cosmética e alimentícia - Rocha, Zelita Maria Santos (2024)
Algae are used worldwide in a range of activities and have great prospecting potential in the pharmaceutical, cosmetic and food industries. In the group of marine macroalgae, the red algae Gracilaria birdiae (GB) is present on the coast of Rio Grande do Norte, being cultivated by the Associação de Maricultura e Beneficiamento de Algas de Pitangui (AMBAP), located on Pitangui beach in Extremoz/RN. GB is an important object of research for the food industry as it is a source of proteins and polysaccharides that are poorly digestible by the enzymes of the gastrointestinal tract, thus constituting a food rich in fiber and excellent for the functional diet as it is also a source of protein. However, algae are still little explored by the Brazilian food industry due to being a product poorly adapted to the Brazilian palate with food resistance to its smell and flavor. Therefore, the research challenge was to produce GB extract using an innovative fermentation technique. removing the smell and reducing its sharp taste, but maintaining its nutritional value, 5 final food products and a cosmetic product, based on GB. The algae biomass obtained can be used in the production of pastes; bakery products in general; dairy and a lot, especially, in vegan products like seaweed yogurt. The research also comparatively evaluated the cultivation techniques by AMBAP and the “Haenyeo” women on the island of Jeju in South Korea. As a final result of the comparison, a manual of conduct was produced with good techniques for managing and manipulating algae to be delivered to AMBAP women.